Progress on outbound tourism expenditure research: A review - Mehran, Javaneh; Olya, Hossein G. T. (Routledge Journals, Taylor & Francis Ltd, 2019)
This study aims to identify how the paradigm of outbound tourism expenditure (OTE) research transforms from economic to social concern. It also explicates the evolution of OTE from an advocacy platform to a sustainability platform. This study adopts a hybrid of narrative and systematic reviews to study OTE as a complex social phenomenon. This hybrid review is complemented by a thematic review and semantic network analysis on gaps and future directions of relevant studies. The results reveal that the paradigm of OTE research is directed from economic toward social thinking. This study proposes an application of socially related antecedent configurations, social theories, pragmatic methods, and various scales of study contexts as promising solutions to address the complexity and heterogeneity of OTE. The study concludes that the conceptual structure of OTE is premised on a sustainability platform, which is influenced by socio-cultural, environmental, economic, and political issues. This study provides a road map that enlightens the current state of OTE, prevailing topics, and pathways for further research.
Keywords: Outbound tourism expenditure; social paradigm; sustainability platform; hybrid review; semantic network analysis; global issues